Desenvolvimento de filamento compósito de matriz termoplástica de PLA com reforço híbrido de fibras curtas de carbono e contínuas de Kevlar29 para manufatura aditiva por extrusão de material - Menezes, Lucio Roberto de (2023)
The present study permeates the frontier of additive manufacturing (AM) by extruding composite materials with continuous reinforcement (Continuous fibers reinforced polymer - CFRP). The growing demand for the development of composites with greater capacity for mechanical resistance due to relative density that meet the needs of projects in the aeronautical and automobile industries, for example, has fostered research around the world on this technology. The current world scenario of technology still has a small number of startups and companies, thus resulting in the opportunity to study and apply it in Brazil. The current stage of CFRP AM by extrusion of material in desktop printers with Cartesian axis presents a fiber volumetric fraction (Vf) of 30%, non-homogeneous reinforcement distribution and the presence of voids. This research aimed to develop and characterize a composite filament of thermoplastic PLA matrix and hybrid reinforcement of short carbon fibers and continuous Kevlar29. With the purpose of application in AM by material extrusion, PLA, short carbon fibers, Kevlar29 and the composites produced were characterized by FTIR-ATR, TGA, DSC, mechanical tensile test, XRD, SEM and µCT. The TGA and DSC results indicated the ideal drying temperature for Kevlar29, where the present humidity triggered porosity. SEM and µCT demonstrated the level of impregnation obtained in the manufacture of the composite, which, due to the absence of internal pressure control in the coating chamber, was limited to the external continuous fibers. FTIR-ATR, TGA, DSC, and XRD indicated that the crystalline structure of the matrix and reinforcement were not altered, indicating the non-formation of adhesion between the phases of the composite. Mechanical tensile performance demonstrated premature failure of the matrix to separate from the reinforcement. Improvement processes were identified, such as pre-drying the continuous reinforcement and adjusting the sealing of the coating chamber nozzles. The studies pointed out that the result of the manufacture of the composite is in the TRL4 stage of technological development, which means testing the product in the laboratory.